PENERAPAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS VI-B SD - Tanjung, Darinda Sofia; Tamba, Rhodentia Sri Hastuti; Sinaga, Veryaman; Tarihoran, Angel Christina (Universitas Negeri Medan, 2025)
This study aimed to determine the implementation of the Project-Based Learning model to improve natural and social sciences learning outcomes on the material of the six continents in the world. This research method is a classroom action research carried out in a cycle process. The subjects of this study were students of class VI-B of SDN 066650 Medan consisting of 20 students. Data collection techniques used observation, tests, and documentation. The use of the PjBL (Project-Based Learning) learning model can improve student learning outcomes, this is shown in the average value in cycle 1 is 55%, and in cycle 2 is 90%. So, it can be concluded that the results of science learning especially on the material six continents in the world increased after the Project-Based Learning model was applied in class VI-B SDN 066650 Medan.